Implementasi Rapid Application Development (RAD) pada Pembangunan Sistem Inventaris Barang Berbasis Website pada Karang Taruna Cipulir - Saifudin, Aries; Meidiaz Satria, Rafly; Koswara, Robby; Sumarlin, Sumarlin; Desyani, Teti (Program Studi Teknik Informatika Universitas Pamulang, 2023)
After its formation until now Karang Taruna Cipulir 005 has organized many social actions and other community activities, especially for young people, which goes hand in hand with the entry and exit of an inventory of goods. The period that is often faced related to this right is that the data collection and reporting of goods are still carried out manually by recording into the existing record book and requires time which quite long in completing each report. The purpose achieved in this study is help simplify management by organizational administrators managers inventaris data by designing web-based inventory system using Rapid Application Development (RAD) system development model. The results of this study show more efficient management of inventory data.